2021
DOI: 10.22159/ajpcr.2021.v14i10.42819
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evaluation of Chronic Consumption of Monosodium Glutamate on Liver of Wistar Albino Rats

Abstract: Objective: The objective of this study was to determine if there were any harmful effects of monosodium glutamate (MSG) on the liver of Wistar albino rats chronically at three different doses, namely, low, mid, and high doses equivalent to human consumption doses in developing countries. Methods: The Wistar albino rats (n=24) were divided into four groups, namely control, Low dose MSG (180 mg/kg), Mid dose MSG (360 mg/kg), and High dose MSG (720 mg/kg). At the end of the experimental period (120 days), animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The consumption of MSG in animal studies has been shown to be hepatotoxic by altering redox state. This process results in abnormal levels of vital liver enzymes, such as Alanine Transaminase (ALT), Aspartate Transaminase (AST), Alkaline Phosphatase (ALP), albumin, total protein and total bilirubin in the blood [12]. Vitamin C, chemically known as L-ascorbic acid, is a water-soluble compound, which is essential for multiple biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of MSG in animal studies has been shown to be hepatotoxic by altering redox state. This process results in abnormal levels of vital liver enzymes, such as Alanine Transaminase (ALT), Aspartate Transaminase (AST), Alkaline Phosphatase (ALP), albumin, total protein and total bilirubin in the blood [12]. Vitamin C, chemically known as L-ascorbic acid, is a water-soluble compound, which is essential for multiple biological functions.…”
Section: Introductionmentioning
confidence: 99%